Interações e brincadeiras por meio de uma tela? A educação infantil e a pandemia da COVID-19 - Malta, Deise Aparecida Silva (2022)
This thesis proposes a reflection on the experiences of children and their families in carrying out school activities in family settings in the context of the COVID-19 pandemic in 2020 and 2021. We have attempted to understand and analyze the observed interactions with schools, in addition to understanding the routines of these families and identifying their perceptions about the specifics of pedagogical interventions conducted with four- and five-year-old children in collective spaces. The proposed study is characterized as qualitative research and the data are organized and analyzed through content analysis. The collection of field research data was carried out in five schools belonging to the Educational Network of the Municipality of Franca. To obtain the research data, semi-structured interviews were conducted with ten family members, two from each school unit in five regions of the city - North, South, East, West and Central. The data analyzed show that, in addition to disregarding the specificities of raising children, the proposal for distance learning in early childhood education, such as that which occurred in the Franca municipal education network, did not take into account the different realities of families, thereby exacerbating the stress caused by the pandemic households increases. The proposal for distance learning in early childhood education did not guarantee learning rights, it was not possible to guarantee experiences, interactions and games in the proposed distance learning. Thus, the data point to the need for changes in the educational practices offered in the preschool of the Franca/SP Municipal Educational Network, indicating a greater urgency to rethink early childhood education and childhood in the city.